Inulin alleviates metabolic dysfunction-associated steatotic liver disease-induced bone loss potentially by activating the Nrf2/GPX4 signaling pathway - Shaobo Gu; Junzhuo Wang; Kangpeng Zhong; Xuejie Yao; Jinfeng Wen; Dahua Chen; Deyi Yan; Zongkai Zhang; Honghui Chen; Xiaoyun Ding; Siyi Yu; Yi Chen; et al. (Molecular and Cellular Biochemistry, 2026)

In situ trophic modes and metabolic traits of the dinoflagellate Karenia in response to short-term localized warming - Hao Zhang; Xiao Ma; Shufei Zhang; Lingshuai Zhang; Chenhui Xiang; Zhiqin Wang; Lin Zhu; Bowei Gu; Xingyu Song; Honghui Huang; Lijuan Long; Xiaomin Xia (Marine Pollution Bulletin, 2026)

Investigation on improving the high-speed performance of rotary compressor with novel axial-flow type motor rotor - Xiangqi Meng; Jingyang Li; Honghui Gu; Weijia Li; Xiangen Bai; Xiaofeng Xu; Dawei Li; Dongdong Qiao; Kai Shen; Yuejiu Zheng (International Journal of Refrigeration, 2025)

Centennial-scale evolution, source apportionment, and ecological risks of heavy metals in Daya Bay, South China sea - Xiangtian Man; Jian Sun; Yu Xiang; Hong Su; Honghui Huang; Yangguang Gu; Han Zhang; Richard W. Jordan; Shijun Jiang (Environmental Pollution, 2025)

Integrated metabolomics and transcriptomics reveal the nutritional profiles and molecular mechanisms in colored cauliflowers - Xiaoguang Sheng; Mengfei Song; Jiansheng Wang; Huifang Yu; Yusen Shen; Shuting Qiao; Fan Lin; Sifan Du; Honghui Gu (Food Bioscience, 2025)

The Variation in a Fish Egg Community and Its Relationship with Environmental Factors in Daya Bay, South China Sea - Sifan Wang; Fengxia Wu; Yiyong Rao; Huaxue Liu; Shufei Zhang; Ming Dai; Yangguang Gu; Gang Hou; Honghui Huang (Fishes, 2025)
To assess the impact of the marine environment on the community of fish eggs in Daya Bay, we collected fish egg samples across four seasons during 2022. A total of 51 species of fish eggs were gathered. The fish egg community exhibited significant seasonal and spatial variations. The number of fish egg species was highest in spring and lowest in winter, while overall abundance peaked during summer. The abundance of eggs from large economic fish (Sparidae) showed a declining trend; however small pelagic fish (Leiognathidae, Engraulidae) have become dominant over time. Spatially, higher abundance is observed in the inner bay compared to the outer bay, particularly around coastal bank waters, near islands and reefs. Additionally, environmental factors and geographical location significantly influenced the fish egg community. For instance, Stolephorus continentalis and Photopectoralis bindus demonstrated a significant positive correlation with both temperature and water depth; conversely, Acanthopagrus schlegelii exhibited a negative correlation with water temperature.

Fine mapping of a major co-localized QTL associated with self-incompatibility identified in two F2 populations (broccoli × cauliflower and cauliflower × Chinese kale) - Yusen Shen; Jiansheng Wang; Xiaoguang Sheng; Huifang Yu; Ranjan K. Shaw; Mengfei Song; Shiyi Cai; Shuting Qiao; Fan Lin; Honghui Gu (Theoretical and Applied Genetics, 2024)

The anthropogenic effects on organic matter in sediment core based on Bayesian mixing model: a case study of Daya Bay - Xiangtian Man; Honghui Huang; Shijun Jiang; Yangguang Gu; Boguang Wang (Environmental Science and Pollution Research, 2023)

Coastal sediment heavy metal(loid) pollution under multifaceted anthropogenic stress: Insights based on geochemical baselines and source-related risks - Zexing Kuang; Huijuan Wang; Beibei Han; Yiyong Rao; Haixing Gong; Wanru Zhang; Yangguang Gu; Zhengqiu Fan; Shoubing Wang; Honghui Huang (Chemosphere, 2023)

Changes in species abundances with short-term and long-term nitrogen addition are mediated by stoichiometric homeostasis - Tian Yang; Min Long; Melinda D. Smith; Qian Gu; Yadong Yang; Nianpeng He; Chong Xu; Honghui Wu; Leena Vilonen; Jinling Zhao; Anke Jentsch; Qiang Yu (Plant and Soil, 2021)

Biological Risk Assessment of Heavy Metals in Sediments and Health Risk Assessment in Marine Organisms from Daya Bay, China - Zexing Kuang; Yangguang Gu; Yiyong Rao; Honghui Huang (Journal of Marine Science and Engineering, 2020)
The concentrations of heavy metals in sediments and marine organisms in Daya Bay were investigated, and the Monte Carlo method was used to analyze the uncertainty of the results of geo-accumulation characteristics and ecological and health risks. The mean concentrations of metal elements in sediments were in the following order: Zn > Cr > Cu > As > Cd > Hg, while those in marine organisms were Zn > Cu > As > Cr ≈ Cd > Hg. The geo-accumulation index (Igeo) indicated that the primary pollutant was Hg, with 5.46% moderately polluted, and 39.52% for unpolluted to moderately polluted. Potential ecological risks (RI) were between low and high risks, and the contributions of Hg, Cd, and As to ecological risks were 50.85%, 33.92%, and 11.47%, respectively. The total hazard coefficients (THQ) were less than 1, but on the basis of total carcinogenic risks (TCR), the probability of children and adults exceeded the unacceptable risk threshold of 22.27% and 11.19%, respectively. Sensitivity analysis results showed that the concentrations of carcinogenic elements contributed to risk in the order of As > Cd > Cr. Therefore, in order to effectively control heavy metals contamination in Daya Bay, it is necessary to strengthen the management of Hg, Cd, and As emissions.

Diversity of Sicilian broccoli (Brassica oleracea var. italica) and cauliflower (Brassica oleracea var. botrytis) landraces and their distinctive bio-morphological, antioxidant, and genetic traits - Ferdinando Branca; Giuseppina Laura Chiarenza; Chiara Cavallaro; Honghui Gu; Zhenqing Zhao; Alessandro Tribulato (Genetic Resources and Crop Evolution, 2018)

The feather-degrading bacterial community in two soils as revealed by a specific primer targeting serine-type keratinolytic proteases - Zhenhong Gu; Honghui Zhu; Xiaolin Xie; Yonghong Wang; Xiaodi Liu; Qing Yao (World Journal of Microbiology and Biotechnology, 2016)

Initiation and development of microspore embryogenesis and plant regeneration of Brassica nigra - Honghui Gu; Xiaoguang Sheng; Zhenqing Zhao; Huifang Yu; Jiansheng Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Efficient doubled haploid production in microspore culture of loose-curd cauliflower (Brassica oleracea var. botrytis) - Honghui Gu; Zhengqing Zhao; Xiaoguang Sheng; Huifang Yu; Jiansheng Wang (Euphytica, 2014)

Rapid alterations of DNA sequence and cytosine methylation induced by somatic hybridization between Brassica oleracea L. var. italica and Brassica nigra (L.) Koch - Xiaoguang Sheng; Zhenqing Zhao; Huifang Yu; Jiansheng Wang; Honghui Gu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Differentiation characteristics and influencing factors of ecological land rent among provinces in China - Kaisheng Long; Yali Zhao; Honghui Zhang; Ligen Chen; Fangfang Lu; Yuanyuan Gu (Journal of Geographical Sciences, 2013)

Protoplast isolation and plant regeneration of different doubled haploid lines of cauliflower (Brassica oleracea var. botrytis) - Xiaoguang Sheng; Zhenqing Zhao; Huifang Yu; Jiansheng Wang; Zhang Xiaohui; Honghui Gu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Temporal and Spatial Expression of Cyclin H in Rat Spinal Cord Injury - Gang Wu; Jianhua Cao; Chen Peng; Huiguang Yang; Zhiming Cui; Jian Zhao; Qiyun Wu; Jiangli Han; Honghui Li; Xingxing Gu; Feng Zhang (NeuroMolecular Medicine, 2011)